Improving Reading Comprehension of The Eighth-Grade Students of SMP Negeri 19 Palu Through Folklore - Nur Malinda; Mashuri Mashuri; Moh. Abraham Akbar Eisenring; Andi Patmasari (MASI Mandiri Edukasi, 2025)
This study aimed to examine the effectiveness of using folklore in improving the reading comprehension skills of eighth-grade students at SMP Negeri 19 Palu. The research employed a pre-experimental design with a one-group pre-test – post-test model. A total of 23 students were selected through a cluster random sampling technique. The data were collected through a reading comprehension test, administered before and after the treatment. The treatment involved teaching reading comprehension through selected Indonesian folktales, including